Pengaruh Penggunaan Celebrity Instagram Endorser Terhadap Keputusan Pembelian Pada Bisnis Online Di Kota Bandung - Julian, Arsy; Novalia, Nidya; Mursyidah, Desta Sulaesih (Perspektif : Jurnal Ilmu Administrasi, 2021)
In the online era like today, Indonesians prefer to buy and sell products through social media. Instagram is widely used to promote products. Consumer purchasing decisions are very important to be reviewed by the company because it will have an impact on the survival of the company. One important aspect is the Instagram celebrity endorser. The purpose of this study was to determine the effect of using celebrity instagram endorser on purchasing decisions in online businesses in Bandung. The place of research was conducted at Mayoutfit Bandung. This research is a quantitative descriptive study with simple linear regression analysis. The data collection technique is through the distribution of questionnaires distributed to Mayoutfit consumers who use Instagram. The data analysis technique is done by validity and reliability test, descriptive test, classic assumption test, normality test, simple linear regression test, hypothesis test and test coefficient of determination. This study shows the influence of Instagram celebrity endorser on consumer purchasing decisions. Suggestions for future research and practical suggestions will be presented further. Keywords: Celebrity endorser, Instagram, Onlineshop, Purchase Decision